Pengaruh Tingkat Penggunaan Energi Listrik terhadap Pertumbuhan Ekonomi di Indonesia - Ulkya Maisarah; Puti Andiny; Safuridar Safuridar (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Developing and developed countries rely heavily on the use of electrical energy to carry out social and economic activities. The purpose of this study is to analyze economic growth and its influencing factors in the period 2004-2023. This research uses time series data. The data method used is the VECM model. The results of this study indicate that there is a one-way causality relationship between variables. In the short term only CO2 emission variables affect economic growth, while in the long term all variables such as electricity and population can affect economic growth.